Nadwaga i otyłość a niedoczynność tarczycy = Overweight and obesity in hypothyroidism - Katarzyna Szwajkosz; Agnieszka Zwolak; Marta Dudzińska; Joanna Świrska; Anna Oszywa-Chabros; Agnieszka Wawryniuk; Robert Łuczyk; Jadwiga Daniluk (Kazimierz Wielki University, 2016)
Szwajkosz Katarzyna, Zwolak Agnieszka, Dudzińska Marta, Świrska Joanna, Oszywa-Chabros Anna, Wawryniuk Agnieszka, Łuczyk Robert, Daniluk Jadwiga. Nadwaga i otyłość a niedoczynność tarczycy = Overweight and obesity in hypothyroidism. Journal of Education, Health and Sport. 2016;6(7):419-428. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58447 http://ojs.ukw.edu.pl/index.php/johs/article/view/3707       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 21.07.2016.     Nadwaga i otyłość a niedoczynność tarczycy Overweight and obesity in hypothyroidism   Katarzyna Szwajkosz1, Agnieszka Zwolak1,2, Marta Dudzińska1, Joanna Świrska1,2, Anna Oszywa-Chabros1, Agnieszka Wawryniuk1, Robert Łuczyk1, Jadwiga Daniluk1,3   1Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 1Department of Internal Medicine with the Department of Internal Nursing, Faculty of Sciences Health, Medical University of Lublin 2Katedra i Klinika Endokrynologii, Uniwersytet Medyczny w Lublinie 2Department of Endocrinology, Medical University of Lublin 3Katedra Zdrowia, Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej 3Department of Health, the National School of the name of Pope John Paul II of Biala Podlaska           Korespondencja: Katarzyna Szwajkosz Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie ul. Jaczewskiego 8, 20-954 Lublin tel. 81 742 58 25 kszwajkosz@wp.pl           Streszczenie Wstęp. Niedoczynność tarczycy, najczęściej będąca skutkiem przewlekłego autoimmunologicznego zapalenia, jest jedną z najczęstszych patologii gruczołu tarczowego i dotyczy około 2% populacji. Niedobór hormonów tarczycy manifestuje się zwykle zmniejszeniem napędu życiowego, stanami depresyjnymi, pogorszeniem sprawności intelektualnej, nietolerancją niższych temperatur. Patologia ta wiąże się ze zwiększonym ryzykiem  nadwagi lub otyłości, wtórnie do zwolnionego metabolizmu, a także jest czynnikiem sprzyjającym hiperlipidemii, co wiąże się ze wzrostem ryzyka sercowo-naczyniowego. Celem pracy była ocena występowania nadwagi i otyłości w grupie pacjentów z niedoczynnością tarczycy. Materiał i metody. W badaniu wzięło udział 101 pacjentów (77K, 24M, w wieku średnio 43 lat) z rozpoznaną niedoczynnością tarczycy. W toku badań zastosowano metodę sondażu diagnostycznego z wykorzystaniem autorskiego kwestionariusza ankiety oraz metodę pomiaru parametrów antropometrycznych, w tym BMI, obwodu talii i bioder. Wyniki. Wśród badanych pacjentów nadwagę (BMI 25-29,9) miało 39,6% badanych, otyłość I stopnia (BMI 30-34,9) 26,7% pacjentów, otyłość II stopnia (BMI 35-29,9)- 10,9%. Wartości BMI≥40 cechujące otyłość III stopnia stwierdzono u 2% badanych. Średnia wartość BMI wyniosła 28,9, przy czym pacjenci w wieku 18-25 lat istotnie częściej cechowali się prawidłową masą ciała niż badani w grupie wiekowej ≥65 lat (p=0,0003), podobnie pacjenci wieku 26-40 lat w porównaniu z badanymi ≥65 lat (p=0,001).  Wnioski. Nadwaga i otyłość dotyczą większości pacjentów z niedoczynnością tarczycy, a ryzyko to rośnie wraz z wiekiem. Wartym rozważenia jest aktywna diagnostyka w kierunku chorób tarczycy wśród pacjentów z nadwagą i otyłością, także w warunkach podstawowej opieki zdrowotnej. Podjęcie prób aktywnego edukowania pacjentów z już zdiagnozowaną niedoczynnością tarczycy z towarzysząca nadwagą i otyłością do zmiany zachowań behawioralnych stanowi wyraz profilaktyki chorób sercowo-naczyniowych.   Słowa kluczowe: otyłość, nadwaga, niedoczynność tarczycy, ryzyko sercowo-naczyniowe.           Summary Introduction: Hypothyroidism is usually caused by chronic autoimmune inflammation of the thyroid gland. It is one of the most common disorders of the thyroid concerning approximately 2% of the adult population. This disorder is related to higher risk of overweight and obesity due to decreased total body metabolism. Furthermore, it predisposes to dyslipidaemia thus increases the risk of cardiovascular disease. Aim: The aim of the study was to evaluate the prevalence of overweight and obesity in patients with hypothyroidism. Material and methods: 101 patients (77F, 24M, with an average age 43years) with diagnosed hypothyroidism were enrolled into the study. A method of proprietary questionnaire was used with measurement of anthropometric parameters. Results: In the examined group of patients, 39,6% were overweight (BMI 25,0-29,9), first degree obesity (BMI: 30,0-34,9) was present in 26,7%; 10,9% of the patients had 2 nd degree obesity. 2% of the examined patients had third degree obesity with BMI ≥40 kg/m2. Mean BMI value was 28,9, whereas patients aged 18-25 years and patients aged 26-40 years had significantly more often normal body mass than patients aged 65 years and older (p=0,0003 and p<0,0001 respectively). Conclusion: Overweight and obesity concern the majority of patients with hypothyroidism and this risk is increasing with patients' age. Therefore, it is worth considering evaluating routinely, also in General Practitioner's office, thyroid function particularly in patients who are overweight or obese. Recognition and treatment of hypothyroidism combined with non-pharmacological actions in overweight and obese patients will be a form of cardiovascular diseases prophylaxis.   Key words: overweight, obesity, hypothyroidism, cardiovascular risk.